2021
DOI: 10.1186/s12916-021-02126-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between cardiometabolic disease multimorbidity and all-cause mortality in 2 million women and men registered in UK general practices

Abstract: Background Myocardial infarction (MI), stroke and diabetes share underlying risk factors and commonalities in clinical management. We examined if their combined impact on mortality is proportional, amplified or less than the expected risk separately of each disease and whether the excess risk is explained by their associated comorbidities. Methods Using large-scale electronic health records, we identified 2,007,731 eligible patients (51% women) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Hypertension is the most significant cause of early death globally [ 53 ] and the first leading risk factor for global disease burden [ 54 , 55 ]. When patients with hypertension occur CMM, it further increases mortality and shortens life expectancy [ 1 3 , 5 ]. Since our results showed that a combination of healthy lifestyle may reduce the risk for CMM in patients with hypertension, any practices and policies that support the adoption of healthy lifestyle factors are encouraged as they will improve the overall health of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is the most significant cause of early death globally [ 53 ] and the first leading risk factor for global disease burden [ 54 , 55 ]. When patients with hypertension occur CMM, it further increases mortality and shortens life expectancy [ 1 3 , 5 ]. Since our results showed that a combination of healthy lifestyle may reduce the risk for CMM in patients with hypertension, any practices and policies that support the adoption of healthy lifestyle factors are encouraged as they will improve the overall health of the population.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of these diseases doubled the risk of mortality. 21 In addition to the increase in mortality from cardiovascular diseases in diabetic patients, it has been observed that they have a higher risk of cancer. Indeed, a systematic review with analysis of 203 cohorts (56,852,381 participants; 3,735,564 incident cancer cases; and 185,404 cancer deaths) that covered the period 1951-2013 found that the relative risk of all-site cancer mortality in diabetics was 1.23 (95% CI, 1.15-1.31).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed a higher risk of mortality in people who at the beginning of follow-up had a history of diabetes (HR, 1.52; 95% CI, 1.51-1.53) or myocardial infarction (HR, 1.51; 95% CI, 1.49-1.52). The combination of these diseases doubled the risk of mortality 21 . In addition to the increase in mortality from cardiovascular diseases in diabetic patients, it has been observed that they have a higher risk of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, except for the limited death numbers, null associations between air pollution and the CMM-death process may be explained by better medical care for CMM patients. A recent study of CMM and mortality in UK general practices have demonstrated that compared with people with individual CMDs, those with multimorbidity could have a higher likelihood of receiving evidence-based treatment to lower the exceeded risk of coexisting cardiovascular and metabolic diseases (33).…”
Section: Discussionmentioning
confidence: 99%